Changes in Retinal Nerve Fiber Layer Thickness after Two Intravitreal Bevacizumab Injections for Wet Type Age-related Macular Degeneration - Entezari, Morteza (J Ophthalmic Vis Res, 2014)
PURPOSE: To evaluate the effect of two intravitreal bevacizumab (IVB) injections on peripapillary retinal nerve fiber layer (RNFL) thickness in patients with wet type age-related macular degeneration (ARMD). METHODS: This prospective interventional case series included 18 eyes of 18 patients receiving two IVB injections within a 6 weeks interval for treatment of wet type ARMD. Peripapillary RNFL thickness was measured prior to the first injection, and 12 and 24 weeks afterwards by optical coherence tomography (3D OCT-1000, Topcon Corporation, Tokyo, Japan). Mean RNFL thickness and values in the four peripapillary quadrants were compared at baseline, and 12 and 24 weeks after initial injection. RESULTS: Mean RNFL thickness was 89 ± 21 μm at baseline which was significantly reduced to 82 ± 15 μm at 12 weeks (P = 0.021). At final follow-up (week 24), mean RNFL thickness reached 87 ± 23 μm and was comparable to baseline values (P = 0.356). Only the temporal quadrant showed a significant reduction in RNFL thickness at 12 weeks (P = 0.033); this quadrant followed the same pattern of change as the mean RNFL thickness, becoming comparable to pre-injection values at 24 weeks (P = 0. 298). CONCLUSION: RNFL thickness may decrease temporarily following two IVB injections in patients with wet type ARMD; however, in the long-term no significant change was detectable from baseline values.